A study of natural enemies of olive leaf gall midge (Dasineura oleae Angelini, Diptera, Cecidomyiidae) as an emerging pest on olive trees in Palestine - Yacoub Batta (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The olive leaf gall midge (Dasineura oleae) is an emerging pest on olive trees in Palestine since the year 2015. This pest infests the leaves, young shoots, inflorescence and fruit stalks of olive trees causing a reduction in the yield. The infestations with D. oleae could be observed on the above-mentioned organs as elongate, indefinite galls. No previous studies were conducted on natural enemies of this pest in Palestine so that the present research aimed at studying the native parasitoids of D. oleae in Palestine in terms of identifying the species of these parasitoids and determining the average percent of parasitism caused by them on D. oleae. Results indicated that there were two species of native hymenopterous parasitoids reared from galls of D. oleae on leaves of olive trees: Platygaster oleae Szelenyi (Platygastridae) and Zeytinus hatayensis Doğanlar (Eulophidae). Certain keys were used for identification of the parasitoids’ species in addition to specific illustrations that were provided in the present study. Results also indicated that the average percent of parasitism caused by these parasitoids were found to be related to the altitudes of the studied olive orchards since the average percent of parasitism was the highest: 69.54-82.36% for P. oleae and 17.64-30.46% for Z. hatayensis at lower altitudes (82-229m above sea level) but it was up to 100% for P. oleae and up to 0% for Z. hatayensis at higher altitudes (492-635m above sea level), respectively. The overall average percent of parasitism was 87.97% for P. oleae whereas, it was 12.03% for Z. hatayensis. These results are promising and might help in developing an effective biocontrol program using these parasitoids as natural enemies of the insect. Such effective use of these natural enemies has been discussed in the paper.